ANALISIS PENGGUNAAN MAJAS DALAM ANTOLOGI CERPEN JEMARI LAURIN TAHUN PELAJARAN 2012/2013 - Zuganda, Yobi; Krisna, Eva; Yulianti, Upit (Pendidikan Bahasa Indonesia, 2013)
This research is motivated by the use of figure of speech writers short stories collected in short story anthologies Laurin fingers . Formulation of the problem in this research is " how the use of figure of speech in a short story anthology Laurin fingers " ? The purpose of this study was to describe the use of figure of speech in the Short Story Anthology fingers Laurin and the dominant figure of speech to describe the short story anthology Laurin fingers . This research is descriptive qualitative research method . The data in this study is a figure of speech figure of speech consisting of comparison , figure of speech conflict , majas engagement , and the figure of speech repetition or affirmation . Sources of data are contained in twenty short stories Short Story Anthology Laurin fingers . Stages of the research done by : ( 1 ) read the short story anthology fingers Laurin , (2 ) literature to find references , guidelines , or references relating to the purposes of the study , (3 ) classifying the data , (4 ) analyzing the data , (5 ) conduct validation of data , (6 ) research concluded , and ( 7 ) writing research reports . In the short story anthology Laurin fingers are 8 kinds of figure of speech . The figure of speech is the personification of 30 times ; figure of speech hyperbole as much as 11 times ; metaphorical figure of speech as much as 6 times ; majas ellipsis 2 times ; simile figure of speech as much as 6 times , as well as sarcasm figure of speech , allusions , and cynicism as much as 1 times . Total use figure of speech in the Short Story Anthology fingers Laurin is 58 times . The dominant figure of speech in a short story anthology is a figure of speech personification Laurin fingers 30 times